Long‐term synaptic depression and memory deficits are reversed by enhancement of GirK‐dependent signaling in a mouse model of early amyloidopathy: Molecular and cell biology/synaptic disruption. (7th December 2020) - Jimenez‐Diaz, Lydia; Sanchez‐Rodriguez, Irene; Djebari, Souhail; Temprano‐Carazo, Sara; Yajeya, Javier; Iborra‐Lázaro, Guillermo; Vega, David; Jimenez, Raquel; Navarro‐Lopez, Juan D.
Abstract: Background: Hippocampal synaptic plasticity disruption by amyloid‐ β (A β ) peptides is thought to be responsible for learning and memory impairments in Alzheimer's disease (AD) early stage. Failures in neuronal excitability maintenance seems to be an underlying mechanism. G‐protein‐gated inwardly‐rectifying potassium (GirK) channels control neural excitability by hyperpolarization in response to many G‐protein‐coupled receptors activation. Method: Here, in early in vitro and in vivo amyloidosis mouse models, we study whether GirK channels take part of the hippocampal synaptic plasticity impairments generated by A β 1‐42 . In vitro electrophysiological recordings from slices showed that A β 1‐42 alters synaptic plasticity by switching high frequency stimulation (HFS) induced long‐term potentiation (LTP) to long‐term depression (LTD), which led to in vivo hippocampal‐dependent memory deficits. Result: Remarkably, selective pharmacological activation of GirK channels with ML297 rescued both HFS‐induced LTP and habituation memory from A β 1‐42 action. Moreover, when GirK channels were specifically blocked by Tertiapin‐Q, their activation with ML297 failed to rescue LTP from the HFS‐dependent LTD induced by A β 1‐42 . On the other hand, the molecular analysis of the recorded slices by western blot showed that expression of GIRK1/2 subunits, which form the prototypical GirK channel in the hippocampus, was not significantly regulated by A β 1‐42 . However, immunohistochemical examination of our in vivo amyloidosis model showed A β 1‐42 to downregulate hippocampal GIRK1 subunit expression. Conclusion: Together, our results describe an A β ‐mediated deleterious synaptic mechanism that modifies the induction threshold for hippocampal LTP/LTD and underlies memory alterations observed in amyloidosis models. In this scenario, GirK activation assures memory formation by preventing the transformation of HFS‐induced LTP into LTD.